(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
This article presents both theoretical and experimental justification of the impact CrossFit training has on fostering a need for physical self-improvement among students in higher education institutions. The author highlights existing shortcomings in the current physical education system at universities. In particular, the standard curriculum includes only two hours of physical education per week for first- and second-year students, while for senior students, physical education is offered only as optional classes, which attract a very small percentage of participants. As a result, the existing approach to student physical education has led to a decline in student sports participation. Many students lack sustained interest in physical activity and do not engage in exercise independently. This situation underscores the urgent need to implement innovative methods that can boost young people’s motivation toward physical activity and a healthy lifestyle. One promising modern approach is the system of high-intensity functional CrossFit training. The author notes that domestic researchers have already demonstrated the positive impact of CrossFit on students’ physical fitness and their attitude toward sports. However, the article also points out the lack of comprehensive research on the long-term effects of CrossFit and the best methods for integrating it into higher education settings. The goal of this study is to help fill this gap by exploring how systematic CrossFit training affects students’ intrinsic motivation to engage in physical self-improvement. The study results show that CrossFit significantly contributes to developing students’ motivation for physical and sports activities. Moreover, it fulfills key personal needs such as the desire for self-development, social interaction, and achieving goals.